2020
DOI: 10.1016/j.molimm.2019.12.013
|View full text |Cite
|
Sign up to set email alerts
|

TLR4 induced Wnt3a-Dvl3 restrains the intensity of inflammation and protects against endotoxin-driven organ failure through GSK3β/β-catenin signaling

Abstract: Background-Accumulating evidence suggests a regulatory role of Wnt proteins in innate immune responses. However, the effects of Wnt3a signaling on TLR4-mediated inflammatory responses are controversial and the signaling crosstalk between TLR4 and Wnt3a remains uncertain.Methods-Gainand Loss-of function approaches were utilized to determine the function of Wnt3a signaling in TLR4-mediated inflammatory responses. Cytokine production at protein and mRNA levels and phosphorylation of signaling molecules were measu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 64 publications
1
22
0
Order By: Relevance
“…The interaction of PAMPs with TLR culminates in the activation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) through the Toll/IL-1 receptor (TIR)-domain-containing adaptors, myeloid differentiation primary response gene 88 (MyD88)-or TIR-domain-containing adapter-inducing interferonb (TRIF)-dependent pathway, which controls the expression of inflammatory cytokine genes (9). The activated state of GSK3b promotes the activation of NF-kB, leading to a proinflammatory response; in contrast, activation of TLR2, 4, 5, 9 by the MyD88dependent signaling pathway promotes the Akt (PKB)-dependent inactivation of GSK3b that leads to an anti-inflammatory response by inactivating NF-kB and activating the cAMP-response element binding protein (CREB), the activator protein 1 (AP-1), the signaltransducer and activator of transcription 1-3 (STAT1-3), the nuclear factor erythroid 2-related factor 2 (Nrf2), and b-catenin (6,7,(10)(11)(12)(13). During viral infection, activation of GSK3b by TLR3/TRIF signaling pathway controls the tumor necrosis factor (TNF) receptor associated factor 6 (TRAF6)-mitogen-activated protein kinase mitogen activated protein kinase kinase kinase (MAP3K7)-(TAK1) and receptor-interacting serine/threonine-protein 1(RIP1)/NF-kB axis to positively regulate pro-inflammatory cytokine production.…”
Section: Gsk3b Transcriptionally Regulates Pro-and Anti-inflammatory Responsesmentioning
confidence: 99%
“…The interaction of PAMPs with TLR culminates in the activation of nuclear factor kappa-light-chain-enhancer of activated B cells (NF-kB) through the Toll/IL-1 receptor (TIR)-domain-containing adaptors, myeloid differentiation primary response gene 88 (MyD88)-or TIR-domain-containing adapter-inducing interferonb (TRIF)-dependent pathway, which controls the expression of inflammatory cytokine genes (9). The activated state of GSK3b promotes the activation of NF-kB, leading to a proinflammatory response; in contrast, activation of TLR2, 4, 5, 9 by the MyD88dependent signaling pathway promotes the Akt (PKB)-dependent inactivation of GSK3b that leads to an anti-inflammatory response by inactivating NF-kB and activating the cAMP-response element binding protein (CREB), the activator protein 1 (AP-1), the signaltransducer and activator of transcription 1-3 (STAT1-3), the nuclear factor erythroid 2-related factor 2 (Nrf2), and b-catenin (6,7,(10)(11)(12)(13). During viral infection, activation of GSK3b by TLR3/TRIF signaling pathway controls the tumor necrosis factor (TNF) receptor associated factor 6 (TRAF6)-mitogen-activated protein kinase mitogen activated protein kinase kinase kinase (MAP3K7)-(TAK1) and receptor-interacting serine/threonine-protein 1(RIP1)/NF-kB axis to positively regulate pro-inflammatory cytokine production.…”
Section: Gsk3b Transcriptionally Regulates Pro-and Anti-inflammatory Responsesmentioning
confidence: 99%
“…Currently, IRAK and TRAF6 are downstream signaling molecules of toll-like receptors (TLR). After LPS infects the body, it first binds to the serum binding protein LPS binding protein (LBP), and transmits to CD14 molecules to produce a LPS-LBP-CD14 complex, which reciprocates TLR4 and its accessory protein myeloid differentiation protein 2, thereby activating IRAK and TRAF6 in succession (35)(36)(37). As an important signaling molecule, IRAK1 exerts a vital part in TLR/IL-1R-mediated innate immune and inflammation response (38).…”
Section: Discussionmentioning
confidence: 99%
“…For example, research in this direction has established the new role of Wnt-β catenin signaling pathway as a negative regulator of LPS-induced TLR4 activation and NF-κB mediated generation of pro-inflammatory immune response without any direct interaction between NF-κB and β-catenin [355] . Also, further study has indicated Wnt3A (Wnt family member 3A) or dishevelled 3 (Dvl3) activates during TRL4 stimulation and inhibits the exaggerated production of pro-inflammatory cytokines (TNF-α, IL-6, and IL-12) and neutrophil infiltration via regulating GSK-β-catenin and NF-κB signaling [356] . In addition, S100 alarmins, comprising of S100 calcium-binding protein A8 (S100A8) [also called myeloid related protein-8 (Mrp-8)] and S100 calcium-binding protein A9 (S100A9) [myeloid related protein-14 (Mrp-14)] are endogenous TLR4 ligands and typically form a heterodimer complex called S100A8/A9 (or Calprotectin) upon their release from myeloid cells [357] .…”
Section: Future Perspective and Conclusionmentioning
confidence: 99%